Insurance Maps of Thomasville, Georgia - Sanborn Map Company (Sanborn Map Company, 1928)
Insurance Maps of Thomasville Georgia, published by the Sanborn Map Company, New York, 1928. With additional indexes added in November 1938 and June 1947. Scanned from original print copy loaned by the City of Thomasville. If you need a higher quality version of this file, please contact archives@valdosta.edu
1 Electronic records. 41 pages, 83 scans. 1 PDF (two copies) 13.9 GB (14,952,611,260 bytes). 212 Files, 3 Folders.
Keywords: Maps; Fire insurance maps; Sanborn Map Company; Thomas County (Ga.); Thomasville (Ga.)